2021
DOI: 10.2298/vsp190507002z
|View full text |Cite
|
Sign up to set email alerts
|

New gold pincer-type complexes induce caspase-dependent apoptosis in human cancer cells in vitro

Abstract: Background / Aim. We investigated cytotoxicity of Au(III) complexes with pincer type ligands against cervical carcinoma cells (HeLa), breast cancer cells (MDA-MB-231 and 4T1) and colon carcinoma cells (HCT116 and CT26). We also examined the type and mechanism of cell death that these complexes induced in cancer cells. Methods.Cytotoxicity of Au(III) complexes was investigated by MTT assay. Apoptosis of treated cancer cells was measured by flow cytometry and applying Annexin V/7AAD staining. The expressions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…Consequently, results have shown the reduction of the amount of antiapoptotic protein Bcl-2 in the presence of complexes 1-3, but there was not emphasized significant reduction in the activation of Bax protein. Complexes 1-3 had a possibility to increase the amount of capsase-3 compared to untreated cells (Zarić et al, 2020). These results confirm a different influence of bulky inert tridentate nitrogen-donor ligand on activity toward different cell lines.…”
Section: Cytotoxic Activity Of Gold(iii) Complexessupporting
confidence: 63%
“…Consequently, results have shown the reduction of the amount of antiapoptotic protein Bcl-2 in the presence of complexes 1-3, but there was not emphasized significant reduction in the activation of Bax protein. Complexes 1-3 had a possibility to increase the amount of capsase-3 compared to untreated cells (Zarić et al, 2020). These results confirm a different influence of bulky inert tridentate nitrogen-donor ligand on activity toward different cell lines.…”
Section: Cytotoxic Activity Of Gold(iii) Complexessupporting
confidence: 63%
“…We suggested that DNA is not the primary target for selected Au(III) and Rh(III) pincer complexes. Among the complexes of various metal ions that we have described in the [42] present review, it appeared that Au(III) pincer complexes are the most potent cytotoxic agents against the studied cancer cell lines. Complex 5 showed the highest cytotoxicity with IC 50 of 0.7 µM against HCT116 cells with apoptosis being the main mechanism of complex-induced cell death.…”
Section: Resultsmentioning
confidence: 77%
“…colon carcinoma (CT26) and breast carcinoma (4T1). [34,42] We then compared the obtained IC 50 values, which are summarized in Table 4. The MTT results revealed that complexes 5-7 and cisplatin, show dose-dependent cytotoxic effects against all tested cancer cells.…”
Section: Bis-pyrazolylpyridine Complexes Of Transition Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature data about proapoptotic mechanism of some gold derivates, also implies activation of caspase-dependent apoptosis, [51] and activation of internal pathway through affecting of mitochondrial membrane potential. [50] This result implies that molecules involved in the internal apoptotic pathway may be an important therapeutic target.…”
Section: Molecular Mechanism Of Induced Cell Death -Apoptosismentioning
confidence: 99%